The Effectiveness of Health Promotion to The Pregnant Womans Attitude in Prevention of Mother to Child HIV Tranmission Examination - Laily Prima Monica (Journal of Ners and Midwifery, 2017)
PMTCT examination is part of the effort to control HIV and AIDS. The ultimate goal is the babies born to mother with HIV liberated from HIV, maternal and infant alive and healthy. PMTCT general policy in line with the policy of the MCH progam with national program to control HIV, other AIDS (Ministry of Health, 2014). The purpose of this study was to determine the effectiveness of health promotion of the attitude of pregnant woman in PMTCT examination. The research design was pre exsperimental with the approach one group pretest postest design. The sample was 15 pregnants woman, choosen by total sampling technique at BPM Lilik, SST Sawentar. The result showed that there was an increase in percent- age of attitude before and after the treatment with positife attitude from 4 people or 26,7% to 9 people or 60%. Based on stastical test Wilcoxon sign rank test obtained p value (0,025) <0,05, it could be concluded that there were an effect of health promotion to the pregnant womans attitude in PMTCT examination. Based the research resulth expectable of pregnant woman more active to increase knowledge by obtaining information about the type of pregnant woman examination, especially about PMTCT examination until it can influence their attitude and increase their conscious to make do PMTCT.